SERIAL FORMATOWANY NA POLSKIM RYNKU TELEWIZYJNYM - Sosnowska, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The television format is happening one from the most of species popular forms on television. Many programs formatted as the reality show exist, talent show, television quiz shows, talk show or specialist programs. It is possible to observe the same scheme in the area of the film and the TV series. A diagnosis of the phenomenon with which formatted series are based on the specific script scheme is a purpose of the article. Described types of formatted series and their meaning of the Polish television production.